2017
DOI: 10.1007/s00464-017-5900-7
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic treatment of leaks after laparoscopic sleeve gastrectomy using MEGA esophageal covered stents

Abstract: Sealing leaks occurring after sleeve gastrectomy with MEGA stents represent an effective method and should become the technique of choice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 12 publications
4
14
0
Order By: Relevance
“…Endoscopic stent implantation successfully treated GL in 69.6% of our patients. This result is consistent with published studies (success ranging from 65 to 100%) [9][10][11][12][13][14][15][16][17][18][19][20][21][22]32] and with systematic reviews (up to 87.8%) [33]. However, in cases where stent therapy was performed with a MS, the success rate was significantly higher (90.9 vs. 50.0% respectively, p = 0.006), which is also in line with the available literature [10-13, 15-20, 34-40].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Endoscopic stent implantation successfully treated GL in 69.6% of our patients. This result is consistent with published studies (success ranging from 65 to 100%) [9][10][11][12][13][14][15][16][17][18][19][20][21][22]32] and with systematic reviews (up to 87.8%) [33]. However, in cases where stent therapy was performed with a MS, the success rate was significantly higher (90.9 vs. 50.0% respectively, p = 0.006), which is also in line with the available literature [10-13, 15-20, 34-40].…”
Section: Discussionsupporting
confidence: 91%
“…facilitating rapid and effective treatment [9][10][11][12][13][14][15][16] and delivering success rates ranging from 67 to 100% [9][10][11][12][13][14][15][16][17][18][19][20][21][22]. Several studies have clearly demonstrated the advantages of stent therapy which include [23] (i) a reduction in the number of procedures/interventions required, including endoscopies and stent changes, (ii) earlier resumption of oral nutrition and (iii) a significant reduction in the duration of hospital stay.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the novel double bump design of the Beta stent, migration occurred in 32% of patients (in 5 patients endoscopic repositioning was possible) which remains comparable to migration rates in FCSEMS [65]. Similar high rates of migration were reported by Klimczak et al (46.1%) [67] and van Wezenbeek et al (66.7%) [66] utilizing bariatric specific stents. These findings of high migration rates in bariatric specific stents underscore that the experienced endoscopist may achieve clinical success not on the reliance of one intervention, but rather with a multimodality approach.…”
Section: Stents For Acute or Chronic Leakssupporting
confidence: 67%
“…In the setting of worrisome clinical signs and normal imaging, laparoscopic or open operative exploration is warranted to rule out GI leak . Nonoperative methods of GI leak treatment after both RYGB or SG include endoscopic endoluminal self‐expandable stents, clips and sutures, endoscopic and percutaneously placed drains, and biologic glue/tissue sealants . Because length of hospital stay after bariatric surgery continues to decrease with the use of ERABS, some septic complications will occur after the relatively earlier hospital discharge .…”
Section: Executive Summarymentioning
confidence: 99%